Theory-based Analyses of Interorganisational Standards for Self-organising, Adaptive Value Creation Networks - Becker, Jörg; Matzner, Martin; Voigt, Matthias (Electronic Communications of the EASST, 2010)
Today many enterprises find themselves in situations of forming new or integrating into existing value creation networks to strengthen their market position and to provide new innovative customer solutions to its customers. Due to their high complexity, effective and efficient value creation networks rely on self-organising and adaptive structures and processes. Information flows amongst business partners and the coordination of these flows by cooperation activities are major design parameters of such networks. Interorganisational standards (IOS) seek to ease information infrastructure design by providing a referential frame. However, practitioners finding themselves in situations of selecting specific standards and thereby deciding against others, so far lack sufficient theoretical guidance in this selection problem. This research informs the IOS selection problem by condensing insights from the body of knowledge from management cybernetics and coordination theory and identifying first requirements to a method guiding IOS choices.